2013
DOI: 10.4103/0972-5229.120318
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality and length of stay in hospitalized cases of 2009 influenza A (H1N1): Experiences of a tertiary care center

Abstract: Aim:To study the clinical characteristics and outcome of admitted patients of H1N1 (hemagglutinin -H neuraminidase -N) influenza in a tertiary level hospital, from Oct 2009 to Dec 2010.Materials and Methods:A retrospective analysis of 77 confirmed patients admitted in this unit with H1N1 infection.Results:Of the 77 patients studied, 33 (42.8%) were female. Mean age was 40.88 ± 13.45 years, majority (70.13%) being less than 50 years. Thirty eight (49.3%) patients had at least one co-morbidity, diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This is possibly because both of these studies looked only at specific causes of fever that can be related to lower platelet counts in advanced stages. Respiratory conditions like pneumonia are among the top conditions associated with prolonged hospitalization [ 19 - 20 ], which was also found in our study.…”
Section: Discussionsupporting
confidence: 86%
“…This is possibly because both of these studies looked only at specific causes of fever that can be related to lower platelet counts in advanced stages. Respiratory conditions like pneumonia are among the top conditions associated with prolonged hospitalization [ 19 - 20 ], which was also found in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Fourteen studies assessed individuals with H1N1pdm09 virus infection, 1 study assessed individuals with H7N9 virus infection, and 4 study assessed individuals with inter-pandemic influenza virus infection. Eight studies (1956 individuals) had useable data related to patients with ARDS 9,10, [14][15][16][17][18][19] . Fourteen studies (n = 6335) reported mortality associated with adults only.…”
Section: Resultsmentioning
confidence: 99%
“…Overall mortality in the included studies. Mortality data were reported in 15 studies [8][9][10][14][15][16][17][18][19][20][23][24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, controversy exists regarding whether these viruses increase the severity of illness and LOS [2]. It has been reported that, while co-infections do not affect LOS or mortality, influenza virus (INF) infection is associated with increased LOS and mortality [3,4]. Nonetheless, the impact of co-infections is, in general, still unclear [2,[5][6][7].…”
Section: Increased Severity Of Viral Infections Has Recently Been Repmentioning
confidence: 99%